2016
DOI: 10.1007/s00382-016-3178-4
|View full text |Cite
|
Sign up to set email alerts
|

Regime shift of the South China Sea SST in the late 1990s

Abstract: regime shift coincides with the switching of pacific decadal oscillation from a warm to cold phase in the late 1990s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…As a result of the much faster warming rate, MHWs have longer durations and are more frequent with greater extension and intensity in the marginal seas of China (Yao et al 2020). Thompson et al (2017) observed a remarkable warming trend in the South China Sea (SCS) since 1997, and SCS MHWs might occur more frequently under global warming (Yao et al 2020). Xiao et al (2020) reported that a record-breaking SCS MHW event in 2015 caused severe coral bleaching on the Dongsha Atoll.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the much faster warming rate, MHWs have longer durations and are more frequent with greater extension and intensity in the marginal seas of China (Yao et al 2020). Thompson et al (2017) observed a remarkable warming trend in the South China Sea (SCS) since 1997, and SCS MHWs might occur more frequently under global warming (Yao et al 2020). Xiao et al (2020) reported that a record-breaking SCS MHW event in 2015 caused severe coral bleaching on the Dongsha Atoll.…”
Section: Introductionmentioning
confidence: 99%
“…Neither WNSI nor multiple linear regression of wind stress anomalies representing the local forcing agree well with the winter NEAMS-mean sea levels from 1997 to 1999, when conventional or eastern Pacific-type El Niño (1997)(1998) and La Niña (1998-2000) events occurred, implying certain roles of remote forcing via atmospheric teleconnections in changing the NEAMS sea level during those years potentially relevant to decadal oscillations linked to the NPGO (Figures 7 and 9). This is particularly true considering the footprint of the El Niño Southern Oscillation or regime shift on the YECS during a couple of (but not all) decades [44,45], thereby, suggesting the use of multiple linear regression analyses of local atmospheric pressure anomalies (WNSI) and climate indices (NPGO) for achieving better prediction.…”
Section: Discussionmentioning
confidence: 99%
“…On decadal timescales, temperature follows a staircase-like pattern (Jones, 2012;Reid and Beaugrand, 2012;Jones et al, 2013;Belolipetsky et al, 2015), while over interdecadal timescales, it forms a complex trend (Jones and Ricketts, 2017). Step-like change has been reported for the atmosphere (Chikamoto et al, 2012;Jones, 2012;Belolipetsky, 2014;Belolipetsky et al, 2015;Bartsev et al, 2016;Bartsev et al, 2017;Saltykov et al;Varotsos et al, 2019), oceans (Beaugrand, 2004;Reid and Beaugrand, 2012;Thompson et al, 2017) and in widespread ecosystem and environmental responses coinciding with these changes (Overland et al, 2008;Conversi et al, 2010;Beaugrand et al, 2019). These changes are usually interpreted https://doi.org/10.5194/esd-2021-61 Preprint.…”
Section: Previous Research and Measuring Nonlinear Changementioning
confidence: 99%